Numerical Simulation Analysis of Temperature and Pollutant Concentration Diffusion in the Open Kitchen Cooking Area. (2017) - Xu, Ang; Li, HuiXing; Feng, GuoHui
Abstract: Open kitchen will be a combination of traditional closed kitchen and living space. However, the open kitchen cooking fumes generated during cooking spread indoor and serious damage to the indoor air quality of rest area (including living room, bedroom, etc.). Improper ventilation can not only quickly and effectively remove pollutants, but also to cause two indoor pollution to endanger people's health. Set up the physical model in this study, application of CFD numerical simulation to analyze the temperature and pollutant diffusion in the open kitchen. Simulate the distribution of temperature and pollutant concentration in several different ventilation conditions in the kitchen and adjacent rooms. The comparative analysis of different cases were carried out, the optimal control method of oil fume pollutants in open kitchen was obtained.